Show that:
Question:

Show that: $2\left(\sin ^{6} x+\cos ^{6} x\right)-3\left(\sin ^{4} x+\cos ^{4} x\right)+1=0$

Solution:

LHS $=2\left(\sin ^{6} x+\cos ^{6} x\right)-3\left(\sin ^{4} x+\cos ^{4} x\right)+1$’

$=2\left\{\left(\sin ^{2} x\right)^{3}+\left(\cos ^{2}\right)^{3}\right\}-3\left(\sin ^{4} x+\cos ^{4} x\right)+1$

$=2\left[\left(\sin ^{2} x+\cos ^{2} x\right)\left(\sin ^{4} x-\sin ^{2} x \cos ^{2} x+\cos ^{4} x\right)\right]-3\left(\sin ^{4} x+\cos ^{4} x\right)+1$

$=2\left(\sin ^{4} x+\cos ^{4} x\right)-2 \sin ^{2} x \cos ^{2} x-3\left(\sin ^{4} x+\cos ^{4} x\right)+1$

$=-\left[\sin ^{4} x+\cos ^{4} x+2 \sin ^{2} x \cos ^{2} x\right]+1$

$=-1+1=0=\mathrm{RHS}$

Hence proved.

Administrator

Leave a comment

Please enter comment.
Please enter your name.